Efektifitas Penerapan Aplikasi Lapor Sleman Dalam Mewujudkan Sleman Smart Regency - Fittia Restiane; Eko Priyo Purnomo; Lubna Salsabila (Indonesian Journal on Software Engineering (IJSE), 2020)
Abstract: Smart City as an innovation in overcoming every problem that occurs in the city. In the Smart City concept there are aspects that are Smart Regency. Is a process of management and development of a variety of natural and human resources, Smart Regency provides innovations in information technology-based grievance services, with access to the Sleman Report application, which is online complaints, aspirations, suggestions and criticisms from the public for the government. However, the services provided by the government to the community were not yet fully maximized in its implementation. The purpose of this study is to see the extent of effectiveness in the application of the Sleman Report in realizing Sleman Smart Regency in Sleman Regency. The result is quite effective for the realization of Smart Regency but in its implementation it is felt to be less than optimal because its handling is sometimes problematic. This study concludes the success of the Sleman Report Program for the steps to realize Smart Regency, the success of target users of the Sleman Report and the achievement of the Report Report in realizing the Smart Regency.Keywords: Smart City,Smart Regency, Lapor Sleman.Abstrak: Smart City sebagai sebuah inovasi dalam mengatasi setiap permasalahan yang terjadi di dalam kota. Dalam konsep Smart City terdapat aspek yang ada yakni Smart Regency. Adalah sebuah proses pengelolaan dan pengembangan dari berbagai macam sumber daya alam dan manusia, Smart Regency memberikan inovasi mengenai layanan pengaduan berbasis teknologi informasi, dengan akses aplikasi Lapor Sleman yakni pengaduan, aspirasi, saran dan kritik secara Online dari masyarakat untuk pemerintah. Namun dalam pelayanan yang diberikan pemerintah untuk masyarakat pun belum sepenuhnya maksimal dalam pelaksanaannya. Tujuan dari penelitian ini adalah untuk melihat sejauh mana efektivitas pada penerapan Lapor Sleman dalam mewujudkan Sleman Smart Regencyn di Kabupaten Sleman. Hasilnya cukup efektif untuk terwujudnya Smart Regency namun dalam implementasinya dirasa kurang maksimal karena penanganannya yang terkadang bermasalah. Penelitian ini menyimpulkan keberhasilan program Lapor Sleman untuk langkah terwujudnya Smart regency, keberhasilan target pengguna dari Lapor Sleman dan pencapaian tujuan Lapor Sleman dalam mewujudkan Smart Regency.Kata kunci: Smart City,Smart Regency, Lapor Sleman